Bibliometric Analysis of STEAM Integration in Chemistry Learning at the Secondary Education Level - Meka Deesongkram (Online Learning In Educational Research (OLER), 2025)
This study explores the integration of STEAM (Science, Technology, Engineering, Arts, and Mathematics) in secondary-level chemistry education, focusing on its impact on student engagement and learning outcomes. Specifically, the study aims to identify research trends, contributors, institutions, and prominent themes in this field. A bibliometric analysis was conducted on 53 research articles indexed in the Dimensions database from 2020 to 2024, and data visualization was performed using the VOSviewer tool. The results revealed a significant increase in publications, peaking at 23 in 2024, indicating a growing interest in STEAM methodologies. Notably, Greek authors demonstrated substantial influence, achieving a high citation count of 132 from only two publications, while Indonesia contributed the highest number of documents with 20 publications and 62 citations. Influential journals such as Applied Sciences and Sustainability were identified, alongside trending themes including augmented reality, gamification, and project-based learning. The findings highlight challenges such as students' negative perceptions of chemistry, limited teacher preparation, and the necessity for effective teaching strategies. This study concludes that interdisciplinary approaches foster critical thinking and creativity among students, ultimately preparing them for modern educational demands. Suggestions include strengthening teacher training, encouraging international collaboration, and adopting innovative pedagogical models. The study is limited to the Dimensions database and the 2020–2024 publication period, which may not capture all global research on STEAM integration